Penerapan Strategi Branding dalam Pengembangan Usaha Mikro Aneka Keripik Mama Uni di Kabupaten Fakfak: The Implementation of Branding Strategies for Micro-Enterprise Development: A Case Study of Aneka Keripik Mama Uni in Fakfak Regency - Sakinah, Nur; Saputri , Tri Bata Biru; Ramadhana, Arga; Roy, Andi (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2026)
According to Law No. 20 of 2008, micro enterprises in Indonesia are defined as businesses owned by individuals or sole proprietorships meeting specific asset and turnover criteria. Aneka Keripik Mama Uni, an micro enterprise that has operated for 10 years in Fakfak Regency, yet it still face challenges such as weak branding and limited distribution channels. This community service project aims to provide recommendations and implement effective branding strategies to support the partner's business development. The results demonstrate a significant branding transformation through the rebranding of the business to Camilan Baye. The strategy implementation encompasses the development of five core components: brand identity, brand image, brand personality, brand positioning, and brand elements. Specifically, the program produced modern and informative packaging designs for five product variants Garlic Peanuts, Hidden Peanuts, Fried Spicy Taro, Banana Chips, and Garlic Sticks complete with the Indonesian Halal logo, "100% Indonesia" labels, and clear contact information. Furthermore, marketing reach was expanded through Facebook social media optimization and the creation of offline promotional media in the form of standing banners. The implementation of this activity has successfully enhanced the partner's knowledge, skills, and capabilities in visual trend-based product design and marketing digitalization to support business sustainability in a competitive market.